OzoNews Volume XX - 15 October 2020 - United Nations Environment Programme (2021)
In this issue: 1. A tribute to Professor Mario Molina, our most esteemed champion of ozone layer protection 2. Kigali Amendment latest ratifications 3. Contingency meeting plans for 2020-2021: update 4. 2020 Antarctic ozone hole is large and deep 5. The 2018 RTOC assessment report mobile air conditioning (chapter 10) 6. Climate-friendly cooling to help ease global warming 7. The IIR launches a call to action to adopt 5 internationally established refrigeration terms 8. A comprehensive quantification of global nitrous oxide sources and sinks 9. Procurement Recommendations for Climate Friendly Refrigerants 10. ECA meeting: Risk analysis - are Article 5 group 1 countries on track to meet the HFC freeze in 2024? 11. More climate-friendly alternatives to harmful greenhouse gases used in air-conditioning and switchgear 12. Suppression de la taxe sur les HFC, initialement prévue pour 2021 (France) 13. Great Britain regulation of F gas and ODS (as of 1 January 2021)